2005
DOI: 10.1007/s00125-005-1962-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMP-activated protein kinase in the coordinated expression of genes controlling glucose and lipid metabolism in mouse white skeletal muscle

Abstract: Aims/hypothesis: AMP-activated protein kinase (AMPK) regulates metabolic adaptations in skeletal muscle. The aim of this study was to investigate whether AMPK modulates the expression of skeletal muscle genes that have been implicated in lipid and glucose metabolism under fed or fasting conditions. Methods: Two genetically modified animal models were used: AMPK γ3 subunit knockout mice (Prkag3 −/− ) and skeletal musclespecific transgenic mice (Tg-Prkag3225Q ) that express a mutant (R225Q) γ3 subunit. Levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…As for LDH isoenzyme system, Long et al (2005) have demonstrated a role of AMPK in the expression of LDH-B subunit in white skeletal muscle cells in mice. On the other hand, Putman et al (2003) have demonstrated that the long-term stimulation with AICAR reduces total LDH activity in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…As for LDH isoenzyme system, Long et al (2005) have demonstrated a role of AMPK in the expression of LDH-B subunit in white skeletal muscle cells in mice. On the other hand, Putman et al (2003) have demonstrated that the long-term stimulation with AICAR reduces total LDH activity in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PRKAG3-associated activity in skeletal muscle may also contribute to changes in LDLcholesterol serum levels. Beyond SREBP1 transcription [36], PRKAG3 regulates gene expression of various glucose-and lipid-metabolic key enzymes in white skeletal muscle [37] and therefore may have an effect on endogenous skeletal muscle cholesterol synthesis and LDL receptor expression. Such changes in cholesterol synthesis or LDL receptor expression of myocytes could alter their LDL-cholesterol ingestion, subsequently also altering serum LDL-cholesterol levels, as skeletal muscle tissue accounts for ∼5% of total peripheral LDL-cholesterol uptake [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose deprivation has also been reported to activate an AMPK pathway [12], which enhances transcription of genes involved in lipid and glucose metabolism [13]. We have recently reported that glucose deprivation enhances the expressions of more than 60 genes including asparagines synthetase to protect the cells from apoptosis induced by glucose deprivation [14].…”
Section: Introductionmentioning
confidence: 99%